Inventory Calculation System by Predicting The Amount of Sales of The Eye Shop Using The Moving Average Method - Charles Hidayat; Pahrizal Pahrizal (Penerbit Jurnal Indonesia, 2022)
For a company, inventory is an asset that is quite large in value. The existence of inventory in a company implies whether there is an inventory or not. Business is an activity in the field of trade with the intention of making a profit. There are various types of businesses that are around us. Inventory is one of the current assets that must be managed properly, especially for the type of business that has an inventory of merchandise. Inventories that are owned by this type of business will be able to be determined at the cost of the inventory and the value of the inventories will be presented on the balance sheet. In calculating the value of the company's inventory, the company can use three methods, namely the FIFO, LIFO and Average methods. The moving average method is used if the past data is data that does not have an element of trend or seasonal factors. Moving average forecasting is widely used to determine the trend of a time series. The main purpose of using moving averages is to eliminate or reduce randomness in the time series. So that it can provide information on incoming and outgoing goods based on transaction reports so that it can predict the number of sales in the next period. It is hoped that this application will always be up to date so that this application follows the development of sales information technology based on Android Flutter.